GoSAMTs are required for pectin methyl-esterification and mucilage release in seed coat epidermal cells - Parra-Rojas, Juan Pablo; Sepúlveda-Orellana, Pablo; Sanhueza, Dayan; Salinas-Grenet, Hernán; Temple, Henry; Dupree, Paul; Saez-Aguayo, Susana; Orellana, Ariel (Frontiers in Plant Science, 2023)
GoSAMTs are required for Golgi-synthesized polysaccharide methylation. Pectin homogalacturonan (HG) methyl-esterification is essential for the proper function of this polysaccharide in cell walls. Several studies have utilized the epidermal cells of seed coats to investigate HG methyl-esterification, because these structures produce mucilage, which is a pectic matrix. To better understand the role of GoSAMTs in HG biosynthesis, we analyzed mucilage methyl-esterification in mutant gosamts. In addition to morphological differences on the seed surface; we observed delayed, uneven mucilage release that was most notable in gosamt1-1gosamt2-1 and changes in the distal wall length indicating abnormal cell wall breakage in this double mutant. Methanol release and immunolabeling with antibodies that recognize high- or low-methyl-esterified HG confirmed GoSAMT1 and GoSAMT2 are involved in HG methyl-esterification in mucilage; we did not, however, find evidence of decreasing HG in the gosamt mutants. Confocal microscopy analyses detected different patterns in the adherent mucilage and a greater number of low-methyl-esterified domains near the seed coat surface, which correlates with greater number of “egg-box” structures in this region. Even though we did not observe apparent changes in the polysaccharide content of the mutants, we detected a shift in the partitioning between the Rhamnogalacturonan-I soluble and adherent layers of the double mutant; interestingly, this change correlated with increased amounts of arabinose and arabinogalactan-protein in adherent mucilage, which suggests compensation mechanisms were triggered in the gosamt mutants. These results demonstrate HG is synthesized in gosamt mutant plants with a lower degree of methyl-esterification; as a consequence, there are more egg-box structures, which produce stiffer cell walls in epidermal cells and alter the rheological properties of the seed surface.